APPLICATION OF THE NUMERICAL MODELING METHODS TO THE TASK OF CHOICE OF THE CHILL ACCESSORY VENT HOLES - A. N. Chichko; T. V. Maljushinets; S. G. Lihouzov (Литьë и металлургия, 2007)
The new method of choice of vent holes on the basis of numerical modeling, differing from the known ones by accounting of dynamics of gas phase, determined by modeling of the chill filling with metal, what allows to minimize the formation of gas defects in casting, is offered.